Growth performance of Monosex Nile Tilapia (Oreochromis niloticus) juveniles at different stocking densities in cages at Lake Bunyonyi in South Western Highland Agro-Ecological Zones (SWHAEZs) - Kwikiriza, Gerald; Barekye, A.; Muhereze, R.; Makuma, K. A.; Tibihika, P. D. (International Journal of Fishery and Aquatic Studies, 2016)
Stocking density is among the critical factors affecting fish growth. Although cage culture is gravely being promoted by the government, information regarding the impact of stocking density on fish growth performance of juveniles in cages in Uganda is limited. This study examined the growth performance of Monosex Nile tilapia (Oreochromis niloticus) juveniles at various stocking densities in cages. The fish of mean wet weight and total length of 1.1±0.1g and 1.3±0.1cm respectively were transferred from nursing ponds in aerated containers to experimental cages at three stocking densities (1000, 1250 and 1500 juveniles/m3). The fish were fed on 45% crude protein formulated diet and total length and wet weight were determined weekly for eight weeks. During each sampling event, water quality parameters (temperature, dissolved oxygen and pH) were measured at the surface and 1.5-2.0 meter depth, before, within and after cages to assess the effect of cages on the water quality in and around the farming area. Results indicate that juveniles stocked at 1000/m3 were significantly heavier and larger than those in higher stocking densities which, in turn were not different from each other. Better performance of fish at lower stocking density could be attributed to availability of space which reduces crowd-related stress, less competition for food and less loss of energy due to the antagonistic behavioral interactions, among others. Likewise, the survival rate was higher (74.0%) at 1000/m3 stocking density than 69.8% at 1250/m3 and 63.1% at 1500/m3 because of reduced mortalities at lower densities. Further, the cage system appeared not to affect water quality parameters measured probably because of low production level and the high circulating nature of water around the farming area. The study demonstrates that increasing stocking density of Nile tilapia juveniles in cages reduces growth and survival rate, hence, growth and survival of O. niloticus juveniles in cages are density-dependent. Thus, culture of Monosex tilapia juveniles at a density of 1000 fish/m3 cages can be considered ideal for augmented production of the fish under South Western Highland Agro-Ecological Zone’s context. However further studies at increased feeding rates are recommended for improved survival and growth rates and thinning of juveniles to avoid wastage of resources.
Keywords: Aquaculture; Cage culture; Growth performance; Condition factor; Nile tilapia; Stocking density; Survival rates